Analysis of the mechanism by which ketamine affects astrocytes in Parkinsonian rats through the PI3K/AKT axis: Effects of ketamine on Parkinsonian rats - Xiong, Yanhong; Yuan, Jianwen; Xu, Luogeng (Cellular and Molecular Biology, 2024)
Parkinson’s disease (PD) remains the most common neurodegenerative disease worldwide, seriously affecting the normal life of patients. Currently, there is no effective clinical cure for PD. In this study, the research team explored the effect of ketamine (KET) on PD, which can lay a reliable foundation for future KET treatment of PD. First, the research team established a PD rat model with 6-hydroxydopamine (6-OHDA). The detection showed that the maximum angle of the inclined plate stay, the number of times of grid crossings and standing, and the ATPase activity in brain tissue were significantly lower in PD rats than in control rats, while the positive rate of α-synuclein in brain tissue was increased, showing typical pathological manifestations of PD. After using KET to intervene in PD rats, the behavioral and brain pathological changes were significantly alleviated, and the inflammation and oxidative stress damage of brain tissue were effectively reduced, suggesting the potential therapeutic effects of KET on PD. Furthermore, the use of KET inhibited the PI3K/AKT axis in the brain tissue of PD rats and promoted autophagy. Moreover, the significant suppression of the PI3K/AKT axis by KET was also demonstrated in the PD cell model established through lipopolysaccharide (LPS) inducement of astrocyte cell line HA1800. It is suggested that the mechanism of KET on PD is related to the inhibition of the PI3K/AKT axis.